Response to 'A clinical and biological review of keratoacanthoma': reply from authors. (1st March 2022) - Tisack, A.; Fotouhi, A.; Fidai, C.; Friedman, B.J.; Ozog, D.; Veenstra, J.
Abstract: Linked Article:  Tisack et al. Br J Dermatol 2021; 185 :487–98 .